PERAN DAN KONTRIBUSI CURAHAN WAKTU KERJA WANITA PADA USAHA PEMBESARAN IKAN PATIN (Pangasius sp) DALAM KOLAM (Studi Kasus Di Desa Pudak Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi) - Asmaida Asmaida; Rogayah Rogayah (Universitas Batangahari Jambi, 2020)
Research was carried out in Pudak Kumpeh Ulu village, Muaro Jambi District. Its goal was 1). Describing the female's role in the pond's catfish farming. 2). To Calculate amount of working duration of female and male in catfish farming in a pond. 3). Analyzing the contributions of female's working duration on a catfish farming in a ponds. The research method used a survey method. It also used a primary and secondary data, with cross section data type based on ratio scale measurement. The population were amount of housewife who did an fish enlargement of the catfish farming in a pond. There were 33 Samples that chosen randomly ones. The descriptive analysis method was used in this research. The results showed that : 1). The role of female on the catfish farming in the pond showed high enough category, females were almost completely involved in pond preparation activities (drying ponds, weaning, fertilization and water giving), seed spreading, feeding, pond- cleaning, and harvesting. 2). The everage of female's work duration on the catfish farming in the pond e.g. 31.48 hours/period in the pool preparation activities (pool drying, sowing, fertilization and water giving), 4.12 hours/period in seed spread, 338.18 hours/period for feeding, 30.91 hours/period in pool- cleaning, and harvesting for 3.36 hours/period. 3). It was 91.17% contribution of female's work duration on the catfish farming in the pond and the remaining as men work duration was 8.83%